2018
DOI: 10.1016/j.bja.2018.05.070
|View full text |Cite
|
Sign up to set email alerts
|

Persistent postoperative pain after total knee arthroplasty: a prospective cohort study of potential risk factors

Abstract: ACTRN12612001089820.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
145
4
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(166 citation statements)
references
References 46 publications
11
145
4
6
Order By: Relevance
“…In rats with preoperative pain, IL-1β, IL6 and TNFα were more highly expressed in the hippocampus of rats (P<0.05). This suggests that preoperative pain can cause a significant inflammatory response in the hippocampus after operation, so we further determined that preoperative pain is an important risk factor for postoperative cognitive impairment [21].…”
Section: Discussionmentioning
confidence: 99%
“…In rats with preoperative pain, IL-1β, IL6 and TNFα were more highly expressed in the hippocampus of rats (P<0.05). This suggests that preoperative pain can cause a significant inflammatory response in the hippocampus after operation, so we further determined that preoperative pain is an important risk factor for postoperative cognitive impairment [21].…”
Section: Discussionmentioning
confidence: 99%
“…The in uencing factors of functional recovery after TKA mainly include the patient's age, sex, preoperative pain level, total duration after TKA and preoperative knee functional state [1,14,15]. There are few studies on the effect of skin temperature on knee joint function, and only a few studies have reported that an increase in the skin temperature can affect the prognosis of knee joint function [1].…”
Section: Skin Temperature and Functional Recoverymentioning
confidence: 99%
“…Insbesondere scheinen hier direkt schmerzbezogene negative Affekte wie Katastrophisieren, Angst oder Hypervigilanz gegenüber Schmerzen entscheidend zu sein [16,22]. Die Vorhersagekraft von Fragebögen, die diese psychologischen Faktoren messen, ist natürlich nicht absolut und nicht vergleichbar mit denen eines diagnostischen Tests -es gibt jedoch erste Belege, dass die Kombination von Fragebögen zu negativen Affekten mit QST-Parametern wie der TS ein prädiktives Potenzial besitzt, das auf klinischer Seite Präventionsmaßnahmen zur Vermeidung von prolongiertem postoperativem Schmerz rechtfertigen könnte [39].…”
Section: Veränderungen Im Gehirnunclassified